Further delineation of eye manifestations in homozygous 15q13.3 microdeletions including TRPM1: A differential diagnosis of ceroid lipofuscinosis. Issue 6 (25th March 2014) - Masurel‐Paulet, Alice; Drumare, Isabelle; Holder, Muriel; Cuisset, Jean‐Marie; Vallée, Louis; Defoort, Sabine; Bourgois, Béatrice; Pernes, Philippe; Cuvellier, Jean‐Christophe; Huet, Frédéric; Chehadeh, Salima El; Thevenon, Julien; et al.
<x xml:space="preserve">Abstract</x> The 15q13.3 heterozygous microdeletion is a fairly common microdeletion syndrome with marked clinical variability and incomplete penetrance. The average size of the deletion, which comprises six genes including CHRNA7, is 1.5 Mb. CHRNA7 has been identified as the gene responsible for the neurological phenotype in this microdeletion syndrome. Only seven patients with a homozygous microdeletion that includes at least CHRNA7, and is inherited from both parents have been described in the literature. The aim of this study was to further describe the distinctive eye manifestations from the analysis in the three French patients diagnosed with the classical 1.5 Mb homozygous microdeletion. Patients' ages ranged from 30 months to 9 years, and included one sib pair. They all displayed a remarkably severe identifiable clinical phenotype that included congenital blindness and convulsive encephalopathy with inconstant abnormal movements. The ophthalmological examination revealed a lack of eye tracking, optic nerve pallor, an immature response with increased latencies with no response to the checkerboard stimulations at the visual evoked potential examination, and a distinctive retina dystrophy with a negative electroretinogram in which the "b" wave was smaller than the "a" wave after a dark adapted pupil and bright flash in all patients. Clear genotype–phenotype correlations emerged, showing that this eye phenotype was secondary to homozygous deletion of TRPM1, the gene responsible for autosomal recessive congenital stationary night blindness. The main differential diagnosis is ceroid lipofuscinosis. © 2014 Wiley Periodicals, Inc.